Organizational architecture of strategic entrepreneurial firms for digital transformation: A bibliometric analysis - Verma, Pratima; Kumar, Vimal; Yalcin, Haydar; Daim, Tugrul (ELSEVIER SCI LTD, 2023)
Organization architecture is the design of an organization that will be able to continuously provide value for present and future firms while optimizing and structuring itself. The study focuses on building blocks for strategic entrepreneurial firms for digital transformation. In the recent era, with volatile customer needs, pandemic situations, and technological development or disruption, organization design has been shifted to a new perspective. Many industry leaders and managers believed industry/firm transformation is associated with the adoption of new technology, but although technologies often play a great role, they have never transformed a firm on their own. Consequently, this study re-actualizes the organizational architecture of digitization and its need for transformation. The discussion starts with a quick overview of the existing literature on organizational design, as well as its key advantages and disadvantages. The study adopted a hybrid approach in the form of a configuration approach and bibliometric methodologies viz. Citation Network Analysis (CNA) and Social Network Analysis (SNA). Based on the hybrid approach, the study identified various dimensions of organizational culture and structure for strategic entrepreneurial firms that deserve to be more careful consideration in digital transformation. The conclusions show that it is necessary to redesign the architecture of the incumbents so that they are ready to embrace the digital environment.
Keywords: Digital transformation; Entrepreneurship; Strategic entrepreneurial firms; Organization architecture; Configuration approach; Bibliometric analysis; OPEN INNOVATION; FAMILY FIRMS; CULTURE; ORIENTATION; TECHNOLOGY; NETWORK; EXPLORATION; PERFORMANCE; LEADERSHIP; ADVANTAGE; Social Issues; Social Sciences - Other Topics